APOE Alleles and Extreme Human Longevity. (27th July 2018) - Sebastiani, Paola; Gurinovich, Anastasia; Nygaard, Marianne; Sasaki, Takashi; Sweigart, Benjamin; Bae, Harold; Andersen, Stacy L; Villa, Francesco; Atzmon, Gil; Christensen, Kaare; Arai, Yasumichi; Barzilai, Nir; et al.
Abstract: We assembled a collection of 28, 297 participants from seven studies of longevity and healthy aging comprising New England Centenarian, Long Life Family, Longevity Gene Population, Southern Italian Centenarian, Japanese Centenarian, the Danish Longevity, and the Health and Retirement Studies to investigate the association between the APOE alleles ε 2 ε 3 and ε 4 and extreme human longevity and age at death. By using three different genetic models and two definitions of extreme longevity based on either a threshold model or age at death, we show that ε 4 is associated with a substantially decreased odds for extreme longevity, and increased risk for death that persists even beyond ages reached by less than 1% of the population. We also show that carrying the ε 2 ε 2 or ε 2 ε 3 genotype is associated with significantly increased odds to reach extreme longevity, with decreased risk for death compared with carrying the genotype ε 3 ε 3 but with only a modest reduction in risk for death beyond an age reached by less than 1% of the population.